2016
DOI: 10.1021/acs.analchem.6b02310
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Glycomic Analyses of Sera Derived from Colorectal Cancer Patients by MALDI-TOF-MS and Microchip Electrophoresis

Abstract: Colorectal cancer is the fourth most prevalent cancer in the United States, yet there are no reliable non-invasive early screening methods available. Serum-based glycomic profiling has the necessary sensitivity and specificity to distinguish disease states and provide diagnostic potential for this deadly form of cancer. We applied microchip electrophoresis and MALDI-TOF-MS-based glycomic procedures to 20 control serum samples and 42 samples provided by patients diagnosed with colorectal cancer. Within the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 51 publications
(127 reference statements)
3
47
0
Order By: Relevance
“…We assigned electrophoretic mobilities to these structures and possible isomers in electropherograms by matching the electrophoretic mobilities of known N-glycans (referred to as electrophoretic mobility standards) to the electrophoretic mobilities of unknown structures. 3940 …”
Section: Introductionmentioning
confidence: 99%
“…We assigned electrophoretic mobilities to these structures and possible isomers in electropherograms by matching the electrophoretic mobilities of known N-glycans (referred to as electrophoretic mobility standards) to the electrophoretic mobilities of unknown structures. 3940 …”
Section: Introductionmentioning
confidence: 99%
“…Enzyme analyses of this type are performed off-line, with any change in the glycan size detected by a shift in the migration time obtained with capillary electrophoresis. [1017] Offline enzyme reactions are conducted for incubation times of several hours and consume significant enzyme quantities. Although most off-line exoglycosidase analyses are performed on glycans derived from glycoproteins, analyses of intact proteins can be accomplished with capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…55 CE compliments the rapid compositional capabilities of MALDI-MS. The microchip electrophoresis can separate structural isomers, which could be more specific toward individual diseases.…”
Section: Methods For Profiling Glycans and Glycoprotein Cancer Markersmentioning
confidence: 99%
“…This study identified tri- and tetra-antennary fucosylated glycans that were significantly elevated in cancer samples when compared to the controls. 55 …”
Section: Methods For Profiling Glycans and Glycoprotein Cancer Markersmentioning
confidence: 99%